Cost-effectiveness analysis of camrelizumab plus paclitaxel and carboplatin versus sintilimab plus gemcitabine and cisplatin or carboplatin for the first-line treatment of local advanced or metastatic squamous NSCLC in Chinese mainland - Liu, Xiaoting; Liu, Xiao-xue; Shao, Wenqing; Zhou, Yi; Zhang, Jing; Zhao, Cuirong; Shen, Chengwu (Frontiers in Pharmacology, 2024)
Objective: Both carelizumab plus paclitaxel and carboplatin (CTC) and sintilimab plus gemcitabine and cisplatin or carboplatin (SGP) have been approved by the National Medical Products Administration of China (NMPA) for the first-line treatment of the local advanced or metastatic sqNSCLC. However, comparison of the two treatments as the first-line treatment in efficacy or pharmacoeconomics has barely been studied. To deeply understand the costs as well as outcomes of the two treatments, this work directly compared the cost-effectiveness for the first-line treatment of local advanced or metastatic squamous NSCLC in Chinese Mainland. Methods: A network meta-analysis was firstly performed based on the three clinical trials: CameL-Sq, ORIENT-12 and C-TONG1002 to compare the clinical benefits of the two treatments. And the Weibull approximation was applied to further calculate life expectancy of the two treatments. The partitioned survival model (PSM) was next established and one-way sensitivity analysis and probabilistic sensitivity analysis were also performed to evaluate the stability of underlying parameter values and assumptions within the model.